SUNFLOWER HUSK RECYCLING AND ENVIRONMENTAL EFFICIENCY: INNOVATIVE APPROACHES (Web of Discoveries: Journal of Analysis and Inventions, 2024)
The increasing volume of sunflower husk byproducts from the agricultural and oil extraction industries has raised concerns regarding environmental sustainability and waste management. This article explores innovative approaches to recycling sunflower husks, focusing on enhancing environmental efficiency and promoting circular economy practices. Key methodologies include their transformation into bioenergy, biodegradable materials, and agricultural fertilizers, leveraging advanced technologies such as pyrolysis, pelletization, and enzymatic treatment. The study highlights the environmental benefits of these recycling processes, including reduced carbon footprint, minimized landfill usage, and energy recovery. By evaluating case studies and emerging trends, the article provides a comprehensive analysis of the economic feasibility and scalability of sunflower husk recycling initiatives. The findings underscore the importance of integrating innovative recycling strategies to achieve sustainable development goals and foster ecological balance.